PERANCANGAN PENGARUSUTAMAAN GENDER DENGAN MENGGUNAKAN WOMEN’S EMPOWERMENT FRAMEWORK DI DESA SENGGRENG KABUPATEN MALANG - Prastiwi, Juwita Hayyuning; Hakim, Andy Ilman (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The community service activity was carried out to encourage gender-responsive policies for the Senggreng Village Government, Sumberpucung District, Malang Regency. The objectives of this activity include obtaining the results of a gender analysis of the existing conditions of female villagers. Second, a design for the implementation of gender mainstreaming must be developed. Third, to convey the results of the PUG assessment to the village government. The gender analysis process was carried out using Longwe's Women's Empowerment Framework (WEF) method, which includes five aspects: welfare, access, awareness, participation, and control. The analysed data was obtained based on two data collection methods: a survey of female villagers and a study of village government documents. The results of the study showed that there were several gender gaps in Senggreng Village, so the final result of this service activity was recommendations based on the three aspects of gender needs, which are specific, practical gender needs, and strategic gender needs. --- Kegiatan pengabdian kepada masyarakat dilaksanakan dalam rangka mendorong kebijakan yang responsif gender bagi Pemerintah Desa Senggreng, Kecamatan Sumberpucung, Kabupaten Malang. Tujuan kegiatan ini antara lain Pertama, untuk memperoleh hasil analisis gender terhadap existing condition warga desa perempuan. Kedua, untuk menyusun perancangan implementasi PUG. Ketiga, tersampaikannya hasil tinjauan PUG kepada pemerintah Desa. Proses analisis gender dilaksanakan dengan metode Women’s Empowerment Framework (WEF) oleh Longwe yang mencakup lima aspek yakni kesejahteraan, akses, kesadaran, partisipasi dan kontrol. Data yang dianalisis, diperoleh berdasarkan dua metode pengumpulan data yakni survei terhadap warga desa perempuan serta studi dokumen pemerintah desa. Hasil analisis menunjukkan adanya sejumlah kesenjangan gender di Desa Senggreng, sehingga hasil akhir kegiatan pengabdian ini adalah rekomendasi-rekomendasi yang disusun berdasarkan tiga aspek kebutuhan gender yakni kebutuhan gender spesifik, kebutuhan gender praktis, dan kebutuhan gender strategis.